2004
DOI: 10.1186/1743-8454-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of connections between cerebrospinal fluid and nasal lymphatic vessels in humans, non-human primates and other mammalian species

Abstract: BackgroundThe parenchyma of the brain does not contain lymphatics. Consequently, it has been assumed that arachnoid projections into the cranial venous system are responsible for cerebrospinal fluid (CSF) absorption. However, recent quantitative and qualitative evidence in sheep suggest that nasal lymphatics have the major role in CSF transport. Nonetheless, the applicability of this concept to other species, especially to humans has never been clarified. The purpose of this study was to compare the CSF and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(201 citation statements)
references
References 35 publications
9
177
1
2
Order By: Relevance
“…Experimental results (Di Chiro, 1964;Orešković et al, 1991;Sato et al, 1972;Sato et al, 1971;Sato and Bering, 1967) also show that CSF is formed outside the brain ventricles (in subarachnoid space). The results also show that CSF absorption occurs not only through villi arachnoidales, but also inside the brain ventricles (Brightman, 1968;Bulat et al, 2008;Cserr, 1971;Dodge and Fishman, 1970;Foley, 1921;Hassin, 1924;Orešković et al, 1991;Wright, 1972), along the nerve roots (Kido et al, 1976), from the subarachnoid space into the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914), and high intraspinal absorption (Edsbagge et al, 2004).…”
Section: The New Working Hypothesis Of Cerebrospinal Fluid Hydrodynamicsmentioning
confidence: 87%
See 1 more Smart Citation
“…Experimental results (Di Chiro, 1964;Orešković et al, 1991;Sato et al, 1972;Sato et al, 1971;Sato and Bering, 1967) also show that CSF is formed outside the brain ventricles (in subarachnoid space). The results also show that CSF absorption occurs not only through villi arachnoidales, but also inside the brain ventricles (Brightman, 1968;Bulat et al, 2008;Cserr, 1971;Dodge and Fishman, 1970;Foley, 1921;Hassin, 1924;Orešković et al, 1991;Wright, 1972), along the nerve roots (Kido et al, 1976), from the subarachnoid space into the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914), and high intraspinal absorption (Edsbagge et al, 2004).…”
Section: The New Working Hypothesis Of Cerebrospinal Fluid Hydrodynamicsmentioning
confidence: 87%
“…Since Shabo and Maxwell (1968) showed that the observed tubular system was probably a consequence of tissue histological preparation, and that the endothelium of arachnoid villi was, in fact, intact (Shabo and Maxwell, 1968), Tripathi and Tripathi (1974) proposed that there are temporary transmesothelial channels which allow the passage of CSF in bulk flow from the subarachnoid space to the venous blood Tripathi and Tripathi, 1974). In addition, there is a large amount of literature which suggests that the significant absorption of CSF (Va) occurs from the subarachnoid space to the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914). Also, in spite of some other proposed places of CSF absorption (choroid plexuses, brain tissue, etc; see later), in physiological conditions the dural sinuses are still the main place of CSF absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a large amount of literature which suggests that a significant amount of the absorption of CSF occurs from the subarachnoid space to the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914). Also, despite some other proposed places (choroid plexuses, brain tissue, etc; see later), in physiological conditions the dural sinuses are still the main place of CSF absorption.…”
Section: Cerebrospinal Fluid Absorptionmentioning
confidence: 99%
“…Drugs that have been taken-up by transcellular diffusion and convection can be adsorbed by the lymphatic or vascular system (and thereby having a low probability of entering the brain) or diffuse to perineural or perivascular spaces and thereby enter the cranial compartment. The perineural spaces of the olfactory and trigeminal nerves seem to allow transport to the CSF of the subarachnoid space [39]. However, some studies suggest that N2B transported substances may be present in the brain without being detectable in the CSF [37].…”
Section: Absorption and Transport Mechanism Of The N2b Routementioning
confidence: 99%